2010
DOI: 10.2174/156652410793384178
|View full text |Cite
|
Sign up to set email alerts
|

Potentialities of Induced Pluripotent Stem (iPS) Cells for Treatment of Diseases

Abstract: Induced pluripotent stem (iPS) cell research has been growing a new height throughout the world due to its potentialities in medical applications. We can explore several therapeutic applications through the iPS cell research. In this review, we have first discussed the development of iPS cells, reprogramming factors, and effectiveness of iPS cells. Then we have emphasized the potential applications of iPS cells in pharmaceutical and medical sectors, such as, study of cellular mechanisms for spectrum of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In addition, zebrafish have a smaller experimental area than other animals, and its genetic ease and other advantages make zebrafish models (MacRae and Peterson, 2015) provide better help for disease research. In addition, zebrafish has many advantages (Lin et al, 2023) over other model animals such as mice, such as in vitro insemination, in vitro development, rapid sexual maturation, high fecundity and low feeding cost (Chakraborty et al, 2009). Finally, zebrafish embryonic development takes place in vitro and the early embryonic body is transparent (Yalcin et al, 2017;Gore et al, 2018), making it suitable for holistic imaging and real-time in vivo observation (Lin F.-J.…”
Section: Melanin Production In Zebrafishmentioning
confidence: 99%
“…In addition, zebrafish have a smaller experimental area than other animals, and its genetic ease and other advantages make zebrafish models (MacRae and Peterson, 2015) provide better help for disease research. In addition, zebrafish has many advantages (Lin et al, 2023) over other model animals such as mice, such as in vitro insemination, in vitro development, rapid sexual maturation, high fecundity and low feeding cost (Chakraborty et al, 2009). Finally, zebrafish embryonic development takes place in vitro and the early embryonic body is transparent (Yalcin et al, 2017;Gore et al, 2018), making it suitable for holistic imaging and real-time in vivo observation (Lin F.-J.…”
Section: Melanin Production In Zebrafishmentioning
confidence: 99%
“…Some experiments using murine embryonic stem cells have shown that a knockout of DGCR8 and Dicer1, two major components of the miRNA silencing complex, causes a defect in stem cell differentiation [ 175 177 ]. According to Chakraborty et al, there are six major factors that are required for pluripotency maintenance, Nanog, Sox2, Oct4, KLF4, Lin28, and c-Myc [ 179 , 180 ].. MiRNA-296, miRNA-470, miRNA-134, and miRNA181a were postulated to be potential targets for these factors and to inhibit stem cells self-renewal [ 181 ].…”
Section: Role Of Emt and Met In Csc Establishment And Progressionmentioning
confidence: 99%
“…[18] Aufgrund der geringen Kosten, der optischen Transparenz und der hohen Reproduzierbarkeit stellen Zebrafischembryonen ein geeignetes System zur Entwicklung von Wirkstofftransporten für verschiedenste menschliche Krankheiten dar. [19] Aus diesem Grund wurde untersucht, ob unser CoiledCoil-System auch in Zebrafischembryonen funktioniert. Soweit wir wissen, wurde die Modifikation der Membran von Zebrafischen bisher noch nicht untersucht (Schema 1 C).…”
unclassified